Study of ocular manifestations of Stevens-Johnson syndrome/toxic epidermal necrolysis - Arundha Abrol; Anirudha Gulanikar; Snehal Thakre; Asim Patel (Wolters Kluwer Medknow Publications, 2020)
Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) represent different ends of the spectrum of the same clinical entity causing severe mucocutaneous reactions, usually to drugs, characterized by intraepidermal cell death leading to blistering and epidermal sloughing. The severe cutaneous manifestations of this disease spectrum may often lead to overlooking of the ocular sequelae, which are very common and may lead to loss of visual acuity. Aim: The present research is an attempt to study the ocular manifestations seen in association with SJS/TEN. Materials and Methods: Patients having ocular manifestations of SJS/TEN attending the outpatient and inpatient department of skin and VD in a tertiary care hospital, were included in the study. Ophthalmologic examination of all patients was observed and recorded. Results: A total of 30 patients were included in the study. Among all, 27 patients had ocular involvement and among them 7 patients (25.9%) had mild, 17 patients (62.9%) had moderate, and 3 patients (11.1%) had severe ocular manifestations. Corneal involvement was found in 12 patients (44.4%), conjunctival involvement was found in 22 patients (81.4%), and eyelid involvement was found in 20 patients (74.0%). All patients were managed medically.